2021
DOI: 10.3389/fonc.2021.644358
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exosomes in Pancreatic Cancer From Bench to Clinical Application: An Updated Review

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains one of the most dismal gastrointestinal malignancies with an overall 5-year survival rate of 8%–9%. The intra-tumor heterogeneity and special tumor microenvironment in PDAC make it challenging to develop effective treatment strategies. Exosomes are extracellular vesicles that originate from the endosomes and have a diameter of 40–160 nm. A growing body of evidence has shown that exosomes play vital roles in tumor initiation and development. Recently, extensive ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…Similar to cfDNA, sensitivity in cancer-specific exosomes has been reported to range widely in PDAC patients, where 50% to 100% has been reported [23]. Exosomal markers have been identified for PDAC diagnosis, recurrence, and prognosis including miR-21, miR-451, miR-196a, miR-1246, and glypican-1 [36]. Isolation methods for exosomes, such as ultracentrifugation are currently inefficient and inconsistent, leading to difficulties in their characterization [37].…”
Section: Liquid Biopsies In Pdacmentioning
confidence: 99%
“…Similar to cfDNA, sensitivity in cancer-specific exosomes has been reported to range widely in PDAC patients, where 50% to 100% has been reported [23]. Exosomal markers have been identified for PDAC diagnosis, recurrence, and prognosis including miR-21, miR-451, miR-196a, miR-1246, and glypican-1 [36]. Isolation methods for exosomes, such as ultracentrifugation are currently inefficient and inconsistent, leading to difficulties in their characterization [37].…”
Section: Liquid Biopsies In Pdacmentioning
confidence: 99%
“…Highly elevated levels of exosomal miR-17-5p and miR-21 were detected in serum samples of pancreatic cancer patients for the first time in 2013 [ 133 ]. Since then, several studies have explored the association of exosomal miRNAs in different stages of pancreatic cancer development [ 38 ]. In pancreatic cancer cells, Sun et al showed that IL-26 level was regulated by the exosomes loaded with miR-3607-3p secreted by natural killer (NK) cells, which suppressed disease progression in vivo [ 134 ].…”
Section: Exosomal Mirnas and Pancreatic Cancermentioning
confidence: 99%
“…The animals survived for a significantly longer time (increased overall survival rate) with no toxic adverse events [ 41 ]. These encouraging results led to a Phase I clinical trial in PDAC patients with a KRAS G12D mutation (NCT03608631) [ 38 ]. After subsequent verification of their safety and efficacy in organoid and patient-derived tumor xenograft models, it can be expected that engineered exosomes can be used as vehicles to deliver miRNAs as therapeutic agents for the targeted treatment of PDAC.…”
Section: Exosomal Mirnas In the Treatment Of Pdacmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes are small membranous vesicles ranging from 40 to 100 nm ( 26 ). They can be used as functional mediators in cell interactions leading to cancer metastasis ( 27 ). Metastasis is a complex multistep process of cancer cell invasion, vascular survival, adhesion and host organ colonization.…”
Section: Introductionmentioning
confidence: 99%